Towards the definition and analysis of social component of sustainable development - Mohamed, Ali Ishag Adam; Mohammed, Mustafa Omar; Barom, Mohd Nizam (2019)
This paper defines social development in the context of sustainable development. To this end, the concept of development and its evolution has been reviewed over the past seven decades. The concept of development has evolved from economic growth to poverty alleviation, sustainable development, human development, and most recently the millennium development goals towards sustainable development goals. A preliminary finding shows that the concept of development has focused more on the economic and environmental aspects in comparison to the social aspect of development. In recent years, however, the concept of sustainable development has begun to emphasis on the social aspect as a fundamental aspect of development. Thereafter, it has gained significant recognition, especially in the World Summit for Social Development in Copenhagen in the late 1990s. However, the definition of social development remains vague and there is no consensus of what perspectives should be adopted in defining social development. Therefore, this paper aims to define and analyse social development from related modern literature on development and argues for the need for a new definition of the social component of sustainable development. Furthermore, the paper adopts meta-analysis and content analysis methods by reviewing and analysing related literature on development from journals, books, conferences, and reports. This study contributes to the existing literature that provides a comprehensive overview of the current understanding of social development and identifies the main propositions of the concept. Besides, the analysis of the existing social component of sustainable development can give insights in developing more comprehensive social development concept in the future.